2020
DOI: 10.3389/fmicb.2020.00888
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of the Escherichia coli O157:H7 Cell Wall and Membranes After Chlorine Dioxide Treatment

Abstract: Treatments of wastewater and fresh produce commonly employ chlorine as an antimicrobial. However, there are increasing levels of concerns regarding the safety and antimicrobial efficacy of chlorine treatments. Numerous studies have reported the antimicrobial properties of chlorine dioxide (ClO 2) treatment in a variety of applications but information regarding how ClO 2 affects bacteria is limited. In the present study, a mixed-method approach utilizing both quantitative and qualitative methodologies was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…Furthermore, loss of cell activity or cell death in ClO 2 -treated Pseudomonas aeruginosa and Staphylococcus aureus is correlated with the increased permeability of inner and outer cell membranes and the subsequent release of vital nuclear materials ( Ofori et al, 2018 ). At higher concentrations, ClO 2 induces accumulation of malondialdehyde (MDA) content, indicating the occurrence of membrane peroxidation ( Bridges et al, 2020 ). However, previous studies based on transmission electron microscopy did not reveal significant morphological damage or cell lysis ( Ofori et al, 2018 ; Bridges et al, 2020 ).…”
Section: Modes Of Chlorine Dioxide Actionmentioning
confidence: 99%
“…Furthermore, loss of cell activity or cell death in ClO 2 -treated Pseudomonas aeruginosa and Staphylococcus aureus is correlated with the increased permeability of inner and outer cell membranes and the subsequent release of vital nuclear materials ( Ofori et al, 2018 ). At higher concentrations, ClO 2 induces accumulation of malondialdehyde (MDA) content, indicating the occurrence of membrane peroxidation ( Bridges et al, 2020 ). However, previous studies based on transmission electron microscopy did not reveal significant morphological damage or cell lysis ( Ofori et al, 2018 ; Bridges et al, 2020 ).…”
Section: Modes Of Chlorine Dioxide Actionmentioning
confidence: 99%
“…However, the use of PMAqPCR shows that leptospiral membranes would not be directly damaged by free chlorine. Several studies have shown that free chlorine inactivates E. coli without damaging its cell membranes [49][50][51][52] further indicating that the use of PMAqPCR is not appropriate to determine the capacity of chlorine to kill bacteria.…”
Section: Plos Onementioning
confidence: 99%
“…In addition, the chlorine treatment can potentially produce carcinogenic compounds, such as trichloramines, as byproducts of the treatment posing public health risks [17,18]. Chlorine dioxide (ClO 2 ) has gained popularity within the last couple of decades to disinfect drinking water and wastewater, and to sanitize fresh produce and poultry [19]. ClO 2 has 2.5 times the oxidizing capability as Cl 2 and may be an effective alternative produce sanitizer [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the efficacy of ClO 2 in reducing human pathogens including Shiga-toxin-producing Escherichia coli, Salmonella enterica, Listeria monocytogenes, Pseudomonas aeruginosa, Staphylococcus aureus, and Yersinia enterocolitica on a variety of produce [19]. The microbial death is believed to be due to oxidation of sulfhydryl groups on cell-surface proteins and increased permeability of the outer membrane [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation